LncRNA LINC00668 promotes cell proliferation, migration, invasion ability and EMT process in hepatocellular carcinoma by targeting miR-532-5p/YY1 axis. Issue 5 (11th May 2020) - Xuan, Wei; Zhou, Chen; You, Guangqiang
Abstract: Liver cancer is now one of the most lethal and commonest cancers in the world, among which over 90% is hepatocellular carcinoma (HCC). Recent studies have confirmed long non-coding RNAs (lncRNAs) are implicated in carcinogenesis. It has been reported lncRNA LINC00668 serves as an oncogene in several cancers. However, the mechanism where LINC00668 regulates HCC is still unclear. qRT-PCR analysis was adopted to detect the expression of relative RNAs. Cytoplasmic and nuclear RNA fraction analysis was conducted to verify the underlying molecular mechanism. Cell colony formation was carried out to test cell colony formation ability and transwell assays were performed to testify cell migratory and invaded abilities. Relevant protein expression level was measured by Western blot assay. LINC00668 was significantly up-regulated in HCC tissues and cell lines. LINC00668 knockdown inhibited cell proliferative, migratory and invasion abilities and slowed down the epithelial–mesenchymal transition (EMT) process. Mechanistically, LINC00668 positively modulates the expression of YY1 by competitively binding to miR-532-5p. It was revealed that LINC00668 up-regulation accelerated cell proliferation and motility in HCC and suggested LINC00668 could be a potential therapeutic target for HCC.